Designing Some Types of Optical Fibers Used in Medical Applications - Ekhlas Mohammed Abd Sahu; Huda Hadi Emmod Abbas; Noor Al-Huda Hassan Rahim Hassoun; Ahmed Abdel Kazem Nasser Bejay; Riyad Karim Jaber Alwan (Genius Journals, 2024)
In this work, several types of optical fibers were designed using the OPTIFIBER program from OPTIWAVE, based on the refractive index formula and the diameter of the core. The types were single-mode step index optical fiber, multimode step-index optical fiber with a fixed refractive index, multimode step-index, and multimode optical fiber. Patterns with a graded-index of refraction. The patterns were shown and their losses were calculated by studying the wavelength of the Nd:YAG laser used in medical devices
Keywords: optical fibers; Medical Applications; wavelength